Ganoderma lucidum: A potential pleiotropic approach of ganoderic acids in health reinforcement and factors influencing their production. (March 2022) - Ahmad, Md Faruque; Wahab, Shadma; Ahmad, Fakhruddin Ali; Ashraf, Syed Amir; Abullais, Shahabe Saquib; Saad, Hisham H.
Abstract: Ganoderma lucidum (G. lucidum) main attractive pharmacological characteristics are antitumor and immunomodulatory activities which are chiefly associated with its two principal bioactive compounds, those are polysaccharides and triterpenoids. Ganoderic acids (GAs) are one of the most discovered triterpenoids of G. lucidum among various triterpenoids. The prominent medicinal mushroom G. lucidum possesses GAs as essential bioactive constituents that are highly oxygenated lanostane-type triterpenoids. GAs exhibit diverse potential action against numerous diseases such as anticancer, antioxidant, anti-inflammatory, anti-HIV, cardioprotective, antiallergic, antihepatotoxic, neuroprotective and antinociceptive properties. GAs act through different mechanisms that include cytotoxic, apoptosis, inducing cell cycle arrest, inhibition of topoisomerases, antiproliferation, anti-invasion, inhibition of NF-kB AP1/uPA, farnesyl protein transferase and JAK-STAT3 pathway. The miraculous effects of GAs fascinate the researchers for their production. Various environmental factors such as biochemical signals, nutritional and physical that influence the biosynthesis of GA. However, the scarcities of pure compounds or accurately characterized extracts are the main problem of clinical studies. Substantial steps are required for characterized extracts of active compounds. This review contributes a thorough insight into the mode of actions of GAs and their possible reinforcements to overcome various diseases.